2016
DOI: 10.1111/acer.12978
|View full text |Cite
|
Sign up to set email alerts
|

Transgenerational Transmission of the Effect of Gestational Ethanol Exposure on Ethanol Use-Related Behavior

Abstract: Background Prenatal alcohol exposure (PAE) enhances the risk for alcoholism by increasing the propensity to consume alcohol and altering neurophysiological response to alcohol challenge. Transgenerationally transmittable genetic alterations have been implicated in these behavioral changes. To date, transgenerational transmission of PAE-induced behavioral responses to alcohol has never been experimentally investigated. Therefore, we explored the transgenerational transmission of PAE-induced behavioral effects a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 50 publications
2
36
0
Order By: Relevance
“…PAE can induce various psychological outcomes, including an increased risk for problematic alcohol use. Interestingly, certain behavioral consequences of PAE can be transmitted from in utero -exposed F1 generation to their F2 and F3 offspring, as our laboratory recently demonstrated (Nizhnikov et al, 2016). Indeed, following prenatal exposure in F1, we found an increase in ethanol intake in F1 through F3 generation infant Sprague Dawley rats, and attenuated sensitivity to ethanol-induced hypnosis in the F1 and F2 generation adolescent male offspring.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…PAE can induce various psychological outcomes, including an increased risk for problematic alcohol use. Interestingly, certain behavioral consequences of PAE can be transmitted from in utero -exposed F1 generation to their F2 and F3 offspring, as our laboratory recently demonstrated (Nizhnikov et al, 2016). Indeed, following prenatal exposure in F1, we found an increase in ethanol intake in F1 through F3 generation infant Sprague Dawley rats, and attenuated sensitivity to ethanol-induced hypnosis in the F1 and F2 generation adolescent male offspring.…”
Section: Introductionmentioning
confidence: 80%
“…The prenatal developmental process of the cerebral cortex is susceptible to PAE-induced disruptions that can last long into adulthood, especially when exposure occurs during late gestation (Miller, 1996, Skorput and Yeh, 2016, Miller, 1986). Therefore, assessing PAE-induced changes in the cerebral cortex may provide valuable insight into changes in motor coordination under the influence of ethanol, such as those previously reported in Sprague Dawley rats (Nizhnikov et al, 2016). …”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Prenatal exposure to low-to-moderate levels of alcohol leads to elevated alcohol drinking in adolescent and adult rodents and even zebrafish (Fabio, Macchione, Nizhnikov, & Pautassi, 2015; Nizhnikov, Popoola, & Cameron, 2016; Sterling, Chang, Karatayev, Chang, & Leibowitz, 2016). Notably, this exposure to alcohol also stimulates the proliferation of OX neurons, subsequently leading to their increase in gene expression and density (Chang, Karatayev, Liang, Barson, & Leibowitz, 2012; Sterling et al, 2016).…”
Section: Role Of Orexin/hypocretin In Non-homeostatic Intakementioning
confidence: 99%
“…Work on the proopiomelanocortin ( POMC ) gene has shown that not only is gene expression downregulated in rats which were prenatally exposed to alcohol, but that the effect of lowered POMC expression can be transmitted through the paternal line to the F2 and F3 generations (Govorko, Bekdash, Zhang, & Sarkar, 2012). Studies have found additional genes with altered expression across generations (Asimes et al, this issue; Popoola, Nizhnikov, & Cameron, this issue; Przybycien-Szymanska, Rao, Prins, & Pak, 2014), as well as altered alcohol drinking-associated behaviors (Finegersh & Homanics, 2014; Nizhnikov, Popoola, & Cameron, 2016), and methylation programming (Asimes et al, this issue; Finegersh & Homanics, 2014). The cross-generational effects on behavior can be dependent on genetic background, as Popoola et al show using rat strains, or conserved across strains, as Rompala, Finegersh, Slater, and Homanics show in mouse models (both in this issue).…”
Section: Prenatal and Preconception Alcohol Exposurementioning
confidence: 99%